Monitoring for Circumstance of Wildfire Occurrence in Kalimantan by Using Satellite Remote Sensing Data Based on GIS - Naru Takayama (JURNAL TERAPAN MANAJEMEN DAN BISNIS, 2018)
Much carbon fixed by forest is emitting as CO2 due to occurrence of wildfire which caused by artificially or naturally. Kalimantan region is one of hot spot the forestry and bio-divergence, however, it is rapidly losing in recent, because deforestation and occurrence of wildfire. Satellite remote sensing is very effective tool to monitor circumstance of ground surface, routinely and extensively. In this report, we tried land cover classification to discriminate burned area for aiming to clarify spatial distribution of frequency of wildfire occurrence. As a result, we could classify land cover to seven types as follow based on discriminate analysis by using multi-band from visible to short wave infra-red acquired from Landsat 8 satellite image; 1. Open water area 2. Cumulus 3. Cirrus or Haze 4. Cloud shadow 5. Vegetation area 6. Other type area 9. No-data. The category 6 of “Other type area” contains city area, bare soil, burned area and edge of cumulus, so we could expect to extract the burned place pixels from this categorical pixels.